9) Calculați : a ) -4+(-3):[2-(-6):(-2)] +1
Răspunsuri la întrebare
Răspuns de
5
a ) -4+(-3):[2-(-6):(-2)] +1 =
-4+(-3):(2-3)+1 =
-4+(-3):(-1) +1 =
-4+3+1 =
-4+4 = 0
-4+(-3):(2-3)+1 =
-4+(-3):(-1) +1 =
-4+3+1 =
-4+4 = 0
carteaocomoara:
MS!
Răspuns de
9
a ) - 4 + ( - 3 ) : [ 2 - ( - 6 ) : ( - 2 ) ] + 1= 0
= - 4 + ( - 3) : ( 2 - 3 ) + 1 =
= - 4 + ( - 3) : ( - 1) + 1 =
= - 4 + 3 + 1 =
= - 1 + 1 =
= 0
= - 4 + ( - 3) : ( 2 - 3 ) + 1 =
= - 4 + ( - 3) : ( - 1) + 1 =
= - 4 + 3 + 1 =
= - 1 + 1 =
= 0
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă